2019
DOI: 10.1002/jhet.3463
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Novel Heterocycles Utilizing 3‐(1,4‐Dioxo‐3,4‐dihydrophthalazin‐2(1H)‐yl)‐3‐oxopropanenitrile as Precursors

Abstract: The reaction of 3‐(1,4‐dioxo‐3,4‐dihydrophthalazin‐2(1H)‐yl)‐3‐oxopropanenitrile 1 and salicyladehyde furnished coumarin derivatives 4 and 5. Coupling reaction of 1 with aryl diazonium chlorides and benzene‐1,4‐bis (diazonium) chloride gave the corresponding hydrazones 6a,b and bishydrazone 9, respectively. Hydrazones 6 underwent intramolecular cyclization upon treating with hydrazine hydrate to give 3‐aminopyrazoles 7. Pyranyl phthalazine 13 was prepared from the reaction of 1 with ethyl 2‐cyano‐3‐ethoxyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing the pyridine pattern have a wide range of biological profiles including antimicrobial 31 36 , anti-viral 37 , 38 , antioxidant 39 , antidiabetic 40 , anticancer 41 43 , anti-inflammatory agents 44 , 45 . For all these benefits related to thiazole and pyridine derivatives and following our work 46 50 , we report here the synthesis of a new library of thiazole derivatives from 1-(3-cyano-4,6-dimethyl-2-oxopyridin-1(2 H )-yl)thiourea 2 .
Figure 2 Structure of amrinone and milrinone.
…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%